1983
DOI: 10.1037/0022-3514.45.3.560
|View full text |Cite
|
Sign up to set email alerts
|

Personal involvement and the robustness of perceptual salience effects.

Abstract: Two experiments were conducted to examine the generalizability of perceptual salience effects. Previous research in social cognition established that "top of the head" processing is a robust inferential bias even in involving task situations. It was expected, however, that perceivers who were personally involved in an issue would be more motivated than less-involved perceivers to shift attention from salient cues to attitudinally congruent but nonsalient message cues. In both experiments, salience was manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 17 publications
5
65
0
Order By: Relevance
“…When setting out to gauge attitude "intensity," some researchers measured certainty (Brim, 1955;Guttman & Suchman, 1947;Katz, 1944;McDill, 1959;Suchman, 1950), whereas others measured extremity (McDill, 1959;Tannenbaum, 1956). To measure "involvement," some researchers assessed importance (Apsler & Sears, 1968;Borgida & Howard-Pitney, 1983;Gorn, 1975; Howard-Pitney, Borgida, & Omoto, 1986), others have assessed knowledge (Stember & Hyman, 1949-1950, and still others measured elaboration (Bishop, 1990;Petty & Cacioppo, 1979). And whereas attitude "salience" has sometimes been measured by indices of importance (Hoelter, 1985;Jackson & Marcus, 1975;Lemon, 1968;Powell, 1977;Tedin, 1980), it has also been gauged by measuring elaboration (Brown, 1974).…”
Section: Common-factor Modelsmentioning
confidence: 99%
“…When setting out to gauge attitude "intensity," some researchers measured certainty (Brim, 1955;Guttman & Suchman, 1947;Katz, 1944;McDill, 1959;Suchman, 1950), whereas others measured extremity (McDill, 1959;Tannenbaum, 1956). To measure "involvement," some researchers assessed importance (Apsler & Sears, 1968;Borgida & Howard-Pitney, 1983;Gorn, 1975; Howard-Pitney, Borgida, & Omoto, 1986), others have assessed knowledge (Stember & Hyman, 1949-1950, and still others measured elaboration (Bishop, 1990;Petty & Cacioppo, 1979). And whereas attitude "salience" has sometimes been measured by indices of importance (Hoelter, 1985;Jackson & Marcus, 1975;Lemon, 1968;Powell, 1977;Tedin, 1980), it has also been gauged by measuring elaboration (Brown, 1974).…”
Section: Common-factor Modelsmentioning
confidence: 99%
“…Likewise, substantial variability exists in both the conceptualizations and operationalizations of strength, which has lead to an extensive array of attitude attributes which have been demonstrated to be consequential for behavior (Krosnick et al, 1993;Chaiken et al, 1995). For instance, investigators have identified attitude importance as a form of strength and shown that this is associated with greater selective perception of information (Krosnick, 1988(Krosnick, , 1990, resistance to social influence (Borgida and Howard-Pitney, 1983) and actual behavior (Jaccard and Becker, 1985). Similarly, other aspects of attitude strength such as certainty (Marks and Kamins, 1988), extremity (Petersen and Dutton, 1975), intensity (Schuman and Presser, 1981) and affectivecognitive consistency have been related to one or more of aforementioned consequences.…”
Section: Conceptualizing Attitude Strengthmentioning
confidence: 99%
“…Extremity or the degree one's ''attitude deviates from the midpoint of favorable and unfavorable toward an issue'' (Krosnick et al, 1993(Krosnick et al, , p. 1132, also has been used frequently to define attitude strength (e.g., Ewing, 1942;Fazio and Zanna, 1978 a, b;Osgood and Tannenbaum, 1955;Peterson and Dutton, 1975). Importance, defined as ''the extent to which an individual cares deeply about and is personally invested in an attitude'' (Krosnick et al, 1993(Krosnick et al, , p. 1133, has been the focus in several studies (e.g., Borgida and Howard-Pitney, 1983;Jaccard and Becker, 1985;Krosnick, 1988Krosnick, , 1990. Ego involvement measures the centrality of one's attitude towards one's self concept and value systems and has been investigated in various studies (e.g., Ostrom and Brock, 1968;Sherif et al, 1973;Spiro and Sherif, 1975).…”
Section: Conceptualizing Attitude Strengthmentioning
confidence: 99%
“…As like source expertise, source attractiveness [29] and the visual prominence [3] have been shown to effectively affect the perception of the message in low elaboration conditions.…”
Section: Using Cuesmentioning
confidence: 99%